Clinical and biochemical comparative study between alternate and every day clofibrate - lovastatin combination therapy on mixed hyperlipidaemia - Al - Mousilly M. Maiada; Al - Kunany A. Bahir (College of Pharmacy / Mustansiriyah University, 2004)
Mixed hyperlipidaemia is the most common form of hyperlipidaemias,where the patients have an elevation in both triglycerides and cholesterol levels with a high risk of atherosclerosis and chronic heart diseases. The therapeutic approach for this disorder described a range from nonpharmacologic lifestyle modifications to newly introduced pharmacologic options.Depending on the basis of recent reports involve fibrate - statin combination and associated with increase the incidence of side effects (myopathy, hepatotoxicity) and therapeutic cost, we suggest and investigate in our study a clinical trial for management of this metabolic disorder by using clofibrate and lovastatin on alternate days instead of the standard daily combination of the same drugs. The study compares the safety, efficacy and cost of both therapeutic regimens for three months follow - up period. A total of 44 patients with a known mixed hyperlipidaemia were enrolled in this study. Of the 40 patients who completed the study, 20 (10 males, 10 females) received alternate - day therapy (group I), their age and weight ranges were (40-65) years and (62-85) Kg, respectively. The remaining 20 (10 males, 10 females) received every day therapy (group II), their age and weight ranges were (42- 67) years and (65-89) Kg, respectively. Ten healthy age - matched control subjects (5 males , 5 females) . The biochemical investigations involve measuring total serum cholesterol, triglyceride, LDL and HDL cholesterol levels as parameters of lipid - lowering agent efficacy; while SGOT,SGPT and CK levels as parameters of safety. All of these parameters were determined at baseline (day 0) and after three months of treatment for both therapeutic groups. The study revealed that there was no significant difference between both treatment groups regarding the percent changes in lipid profiles from baseline values. These profiles had been returned to normal limits in all patients in both groups. The mean of SGOT levels for both treatment groups was significantly higher than that of control, but with group II the extent was more, while for SGPT levels group II only was significantly higher (less safety) than control one. With respect to CK levels and for both treatment groups, only slight elevation (not significant) occurred compared with control, but with group II the extent was more.With group I, the therapeutic cost was reduced by nearly 50% compared with group-II. By this clinical and biochemical trial, we decreased the side effects and cost of fibrate - statin combination while keeping their efficacy in lowering serum lipids.